Implikasi Penetapan Wilayah Pusat Pertumbuhan Industri Terhadap Penggunaan Lahan Di Kabupaten Majalengka - Paramasatya, Albi; Rudiarto, Iwan (Jurnal Pembangunan Wilayah dan Kota, 2020)
Regional development in Indonesia has rapid progress along with the central government's policies in equitable development. Global phenomenon to encourage equitable regional development, each country takes the initiative to develop industrial cluster policies. This study aims to analyze implications of determination a growth centre of industrial region to land use changes. Output of this study expected identify how many area implicated to land use changes and land conversion that occur. This study is located in Majalengka Regency as one of  growth centre of industrial region . The method used in this study is the LULC Method (Land Use Land Changes) and Overlay (Georeferencing) Method. The result shows determination  growth centre of industrial region have implications in land use changes. The implication in the form of considerable land conversion. This implication occurs in locations that are designated as industrial growth centers and around these locations. In addition, the implications of  determination  growth centre of industrial region  are in the form of expansion of land to surrounding industrial areas.